Assessment of stigma and prejudice in the organization of care networks for drug users - Elitiele Ortiz dos Santos; Leandro Barbosa de Pinho; Aline Basso da Silva; Adriane Domingues Eslabão (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To assess stigma and prejudice in the organization of the Psychosocial Care Network for drug users. Methods: this is a qualitative study, developed through Empowerment Assessment. The survey was conducted in a municipality in Rio Grande do Sul, with 42 network workers. For data collection, participant observation, semi-structured interviews and open forum were used. For data analysis, thematic analysis was used. Results: the network's mission involved a proposal for care without prejudice and judgments for drug users. It was identified that the composition of the network with training in multidisciplinary residency and psychiatry facilitates achieving the mission, and among the difficulties, the challenges to overcome prejudice were analyzed. Strategies for continuing education, seminars, and user empowerment in the community are suggested. Final considerations: stigma and prejudice need to be problematized in the networks for the organization of more inclusive and rehabilitating psychosocial care.